PENGARUH LATIHAN SKIPPING TERHADAP PENINGKATAN KELENTUKAN PERGELANGAN TANGAN DAN POWER TUNGKAI PADA ATLET ACADEMY BULUTANGKIS JR19 - Diyanto, Rahmad; Salsabilah; Purwanto; Adha, Arfa; Hilmi Wahdi, Agung; Syaputra, Aidil; Evriansyah Lubis, Ade (JURNAL ILMU KEOLAHRAGAAN, 2024)
This study aims to analyze the effect of skipping training on increasing wrist flexibility and leg power strength in JR19 badminton academy athletes. This study used an experimental approach by measuring significant changes in wrist flexibility and leg power before and after the implementation of skipping training. Sample of 18 people, 10 boys and 8 girls. The research design used One Group Pre test and Post test Desaign. From the results of the prestest descriptive test, the average value of the wrist flexibility test from pre test to post test shows a significant increase. It is known that the sig value (p-value) for testing the pre test with the post test = 0.008, it can be concluded that the sig value (p-value) for testing the pre test with the post test is 0.008 and 0.008 < α = 0.05 so it can be concluded that there is a significant effect of skipping training to increase leg power in JR19 badminton academy athletes. The results of the skipping exercise research have a significant effect on increasing wrist flexibility and leg muscle power in JR19 badminton academy athletes